Pharmaceutical Micropollutants (Antibiotics) in Drinking Water Treatment Plants (WTPs) - MohammadMehdi Fowzi; Ehsan Jafarpisheh; Mohammad Mehdi Amin (Geography, Earth Science and Environment: Research Highlights Vol. 2, 2024)
The presence of pharmaceutical micropollutants, particularly antibiotics, in drinking water, has emerged as a critical environmental issue. These contaminants enter aquatic ecosystems through multiple pathways, including sewage discharge, industrial wastewater, and improper disposal. Antibiotics, due to their persistence, bioaccumulation, and toxicity, pose significant threats to aquatic organisms and human health. This chapter explores a range of topics concerning antibiotics, including measurement techniques, their concentrations in water treatment plants across various countries, methods for their removal in water treatment plants (WTP), and their environmental and health impacts. The chapter also assesses advanced treatment technologies, including membrane filtration, activated carbon adsorption, and advanced oxidation processes, to improve removal efficiencies. Despite these advanced methods, conventional treatment processes remain insufficient in fully eliminating antibiotics from water, underlining the need for more integrative solutions. The chapter discusses the environmental and health impacts, particularly the rise of antibiotic-resistant bacteria and long-term health risks associated with antibiotic exposure. The findings call for enhanced regulatory frameworks and technological advancements to address the persistent issue of pharmaceutical contaminants, particularly antibiotics, in drinking water.